(untitled) (TAMADDUN NURI JURNALI, 2025)
This article presents a formal and functional analysis of parentheticals in M. E. Saltykov-Shchedrin’s novel “The Golovlyov Family”. The study examines the following functional types of parentheticals in the novel: authorial remarks, character replies, metalinguistic and metareflective parentheticals, as well as parentheticals with a primarily communicative function.